Attitude towards breast-feeding amongst Indian working women in the estate (A case study at Cangkat Asa Estate, Tanjung Malim) / Prmasvary Appayee Ayasamy - Prmasvary Appayee , Ayasamy (1988)
This Graduation Exercise is a case study concerning the aspects of infant feeding practices among the Indian working women in Changkat Asa Estate. Specifically, it is about the attitudes of the women towards breast-feeding and their performance. In order to provide a clear and systematic picture, this study is divided into various chapters. Chapter one gives a general introduction of the objective, scope and significance of this study. It also includes the target group chosen, the area selected, the methodology used and lastly the problem encountered in this study. Chapter Two contains the background characteristics of Changkat Asa Estate such as location, history, size, demography and occupational structure. It also touched 011 the aspect of amenities in this estate. Chapter Three presents the definitions of relevant concepts and theories used in this study. Special attention is given to the concept of role. Chapter Four provides the bio-data of the respondents and their families. Matters that are mentioned are age of respondents and their husbands, level of education, the family size and the household income etc. Chapter Five is totally devoted to the findings concerning infant feeding practices. The women's attitude towards breast-feeding and their performance is given emphasis. It also touches on the level of awareness and knowledge of the women concerning breast-feeding and infant formula. The factors which influence determine the women's performance and attitude towards breast-feeding are also mentioned in this chapter. Chapter six provides a summary of the findings and its significance. The relationship between the findings and relevant concepts discussed in chapter Three is also mentioned. This chapter also contains suggestion recommendation put forth to improve the performance of breast-feeding among the women in the estate.